Kepemimpinan Transformational, Keterlibatan Kerja, Motivasi Kerja, dan Kepuasan Kerja Mempengaruhi Kinerja Karyawan - Ayu Giyanisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to know the relationship between transformational leadership, work engagement and work motivation against job satisfaction to enhance the employee performance in one of the public company. The methodology used was Structural Equation Modelling (SEM) by giving questionnaires to 330 operational employee of public company in Indonesia as a research sample. The results showed that transformational leadership did not have direct influence toward job satisfaction. While, work engagement and work motivation had direct influence toward and could enhance the job satisfaction. Moreover, transformational leadership had direct influence against employee performance. Work motivation did not have any direct influence on employee performance, and job satisfaction had influence on the employee performance enhancement. Therefore, it can be concluded that job satisfaction was influenced by work motivation and work engagement, whereas employee performance was influenced by transformational leadership and job satisfaction. Keywords: Transformational Leadership, Work Motivation, Work Engagement, Job Satisfaction, Employee Performance.